A Convenient Approach To Synthesize o‐Carborane‐Functionalized Phosphorescent Iridium(III) Complexes for Endocellular Hypoxia Imaging. Issue 48 (27th October 2016) - Li, Xiang; Tong, Xiao; Yan, Hong; Lu, Changsheng; Zhao, Qiang; Huang, Wei
Abstract: The structure–property relationship of carborane‐modified iridium(III) complexes was investigated. Firstly, an efficient approach for the synthesis of o ‐carborane‐containing pyridine ligandsa –f in high yields was developed by utilizing stable and cheap B10 H10 (Et4 N)2 as the starting material. By using these ligands, iridium(III) complexesI –VII were efficiently prepared. In combination with DFT calculations, the photophysical and electrochemical properties of these complexes were studied. The hydrophilic nido ‐ o ‐carborane‐based iridium(III) complexVII showed the highest phosphorescence efficiency (abs. ϕ P =0.48) among known water‐soluble homoleptic cyclometalated iridium(III) complexes and long emission lifetime ( τ =1.24 μs) in aqueous solution. Both of them are sensitive to O2, and thus endocellular hypoxia imaging of complexVII was realized by time‐resolved luminescence imaging (TRLI). This is the first example of applying TRLI in endocellular oxygen detection with a water‐soluble nido ‐carborane functionalized iridium(III) complex. Abstract : A leading light : A hydrophilic nido ‐ o ‐carborane‐based homoleptic cyclometalated iridium(III) complex was prepared which showed high phosphorescence efficiency (abs. =0.48 in H2 O). It was applied in oxygen detection as well as for revealing intracellular hypoxia by phosphorescence lifetime imaging microscopy (PLIM) and time‐gated luminescence imaging (TGLI; see figure).